Performing the double rupture: Kraftklub, popular music and post-socialist urban identity in Chemnitz, Germany. (July 2017) - Erbacher, Eric; Nitzsche, Sina
Popular music constitutes an important mode of public expression which can stimulate not only a change in the public image of place but also wider social and cultural communities in shrinking cities. Focusing on the internationally successful indie-rap band Kraftklub from the Eastern German city of Chemnitz, we analyse how they visually, rhetorically and musically address shrinkage and the GDR as a critical comment on municipal memory and identity politis. Contextualizing Kraftklub's oeuvre with the official city marketing campaign, we show that popular music scenes help establish a new, inclusive and confident post-industrial identity as well as contribute to a more positive urban image.